A case report of apert syndrome in a 13-year-old girl presenting with dental pain (Journal of Ideas in Health, 2025)
Background: Apert syndrome is a rare congenital craniosynostosis syndrome caused by mutations in the FGFR2 gene, with an incidence of 1 in 65,000 to 200,000 live births. It is characterized by premature cranial suture fusion, midfacial hypoplasia, and syndactyly of the hands and feet. In addition to craniofacial and skeletal anomalies, patients often present with dental, airway, and ophthalmological complications requiring long-term multidisciplinary management.Case Presentation: We describe a 13-year-old female with a known diagnosis of Apert syndrome who presented with progressively worsening dental pain over one month, associated with temporal headaches and difficulty chewing. Examination revealed brachycephaly, midfacial hypoplasia, exophthalmos, and significant oral findings including high-arched palate, malocclusion, and dental crowding. Bilateral surgical scars from previous syndactyly correction were present, with residual deformities of the hands and feet. Laboratory evaluation demonstrated normal thyroid and gonadotropin profiles. Pelvic ultrasound showed normal uterus and ovaries with multiple immature follicles. She was referred for orthodontic assessment and multidisciplinary follow-up.Conclusion: Apert syndrome is a multisystem disorder that requires coordinated, lifelong management. This case emphasizes the importance of early and continuous dental surveillance, endocrinological monitoring, and psychosocial support in optimizing outcomes for adolescents with Apert syndrome.
Keywords: Apert Syndrome, Craniosynostosis, Syndactyly, Dental Crowding, Endocrinology, Iraq